A UNIQUE COLLABORATION: USM FIRST-TIME OFFERING OFF-SHORE ARCHITECTURAL PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 31 August 2015 – For the first time, Universiti Sains Malaysia (USM) is offering an offshore Bachelor of Science Programme (Housing, Building and Planning), with an initial intake of 54 candidates who have completed their Diplomas from Polytechnics throughout the country.